2019
DOI: 10.1177/2156869319894372
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Perceived Public Regard on the Well-Being of Military Veterans

Abstract: Many military veterans face considerable challenges reintegrating into civilian life. Evidence suggests the general public holds conflicting attitudes toward veterans. This study examines how perceived public attitudes play a role in veterans’ mental health and well-being. Drawing from and extending interactionist theories of self-concept, stigma, and mental health recovery, we develop and estimate models for the relationships between internalized public attitudes toward veterans (perceived public regard), mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 67 publications
(84 reference statements)
2
4
0
Order By: Relevance
“…Every path of this model was consistent with the previous findings. The significance of mattering in predicting SWL had been reported by previous studies since before the pandemic [12], [15], as well as our findings that mattering predicts PSS [24]- [26]. Another study during the lockdown in Malaysia also yielded the same findings that PSS partially mediated the link between mattering and SWL [21].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Every path of this model was consistent with the previous findings. The significance of mattering in predicting SWL had been reported by previous studies since before the pandemic [12], [15], as well as our findings that mattering predicts PSS [24]- [26]. Another study during the lockdown in Malaysia also yielded the same findings that PSS partially mediated the link between mattering and SWL [21].…”
Section: Discussionsupporting
confidence: 90%
“…By definition, mattering is a construct that measures how much we feel we matter to others [14]. Mattering was reported as a significant predictor of SWL before the pandemic [12], [15]. Consistently, a study on the formation of SWL during the lockdown in the Malaysian context reported that mattering was a robust significant predictor of SWL, partially mediated by perceived social inclusion among individuals with low and moderate levels of extraversion [16].…”
Section: Introductionmentioning
confidence: 85%
“…However, the current study extends this finding to military veterans and supports the promotion of sport programing to veterans. The positive link between a military identity and life satisfaction while in line with some research (Markowitz et al, 2019) contradicts other research, and a persuasive argument about the negative role of any identity when participants are no longer able to occupy or live a life commensurate with that identity. The most common reason for why a strong military identity may be maladaptive is because veterans no longer fill a military role.…”
Section: Discussionsupporting
confidence: 54%
“…Generally, the lack of appreciation is not unique across extant global armed forces community literature. Vietnam, Iraq and Afghanistan veterans have had hostility directed towards them due to opinions over those military campaigns (45)(46)(47) . Yet, the sense of hostility and disfavour directed at NI veterans is connected to them being representatives of the Crown and not a particular military campaign.…”
Section: Experiential Ndings -Challenging Existing Literaturementioning
confidence: 99%
“…The negativity is perceived to feel a lot more personal, especially among those who served with the UDR. Experiencing a poor sense of self-appreciation, due to public perceptions/interactions, is concerning as it may lead to worse mental health outcomes and fuel self-marginalisation (45) .…”
Section: Experiential Ndings -Challenging Existing Literaturementioning
confidence: 99%